Sundarbans Mangroves of India - a Study on Conservation Status - Chakrabarti, Kalyan (Indian Forester, 1987)
In this paper, an analysis has been made of fauna-flora dynamics generic and species diversity of the animal vegetation complex for the Sundarbans mangroves. Calculations of generic and specific diversities have been made in various types of micro-ecosystems, differentiated on the basis of tidal rhythms with respect to the floral and faunal organisms. Diversities were also computed for fishes, molluscs and crustaceans. Mangrove zone, situated below the tide level was observed to be comparatively rich in generic and specific diversity over other zones which are frequently inundated or above the tide levels. Again the generic diversity of Sundarbans molluscs were found to be more than that of tree vegetation. Crustaceans, fish and other kinds of faunal organisms.